2000
DOI: 10.1258/0022215001903825
|View full text |Cite
|
Sign up to set email alerts
|

Metastases from glomus jugulare tumours

Abstract: This review describes the features of glomus jugulare tumours with metastases. There were 100 sites of metastasis in the 53 cases previously reported. The sites of metastasis may be summarized as bone (33), lungs (23), lymph nodes (19), liver (nine) and other (16). Metastases presented up to 30 years after the initial treatment. The mean age of patients was 45 years and the sex ratio was approximately two females to one male, with no significant difference compared to non-metastatic tumours. There was a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 27 publications
0
25
0
1
Order By: Relevance
“…The findings in our three patients indicate that MRI could be included in the staging of paraganglioma patients with risk factors for malignancy, such as vagal location (2,3), young age (14), or recurrent disease (4), and that the MR appearance of the bone metastatic deposits may be distinctive. However, the appropriate place for an exhaustive MR evaluation of the axial skeleton in staging has to be further discussed in the light of the natural history of bone metastases from paragangliomas, and the treatments that are available.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The findings in our three patients indicate that MRI could be included in the staging of paraganglioma patients with risk factors for malignancy, such as vagal location (2,3), young age (14), or recurrent disease (4), and that the MR appearance of the bone metastatic deposits may be distinctive. However, the appropriate place for an exhaustive MR evaluation of the axial skeleton in staging has to be further discussed in the light of the natural history of bone metastases from paragangliomas, and the treatments that are available.…”
Section: Discussionmentioning
confidence: 72%
“…In a review of the literature from 1945 to 1995, Brewis et al (4) found that one-third of paraganglioma metastases were located in the bone, mainly in the vertebrae and ribs.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Although the commanding majority of glomus jugulare tumors are benign, a small fraction are metastatic. Brewis et al 4 estimated that between 1 and 4% of all glomus jugulare tumors are metastatic, although they note that this may be an overestimate due to preferential reporting of metastatic cases and to clinicians misidentifying benign multicentric glomus jugulare tumors as metastatic.…”
Section: Overview Of Glomus Jugularementioning
confidence: 99%
“…They can also be associated with the tympanic branch of the glossopharyngeal nerve (Jacobson nerve) or the auricular branch of the vagus nerve (Arnold nerve) [2]. Although these are indolent hypervascular tumours, they can be associated with metastatic spread in 1-5% of cases [3]. The growth rate is typically very slow, approximately 0.8 mm per year; however, the pattern of growth is often associated with compression and infi ltration of adjacent bone, cranial nerves and/or blood vessels.…”
Section: Introductionmentioning
confidence: 99%